Interpersonal and academic self-efficacy and its relationship with employment of food industry engineering students: A gender perspective - Reyes-González, Ana M.; Velázquez-Sánchez, Luz M.; Rojas-Parra, Azucena; Chuck-Hernández, Cristina (Frontiers in Education, 2022)
An analysis of self-efficacy and its effect on employment was performed with data obtained from Food Industry Engineering Students (FIES), with strong food engineering and food manufacturing and innovation-related competencies, from 2019 to 2021. The aim was to determine if there is a relationship between self-efficacy and employment in FIES to define potential actions for educational institutions looking to reduce the gender disparity in professional life. Results showed differences in self-assessment categories regarding gender, with men having a better self-perception, especially in economic analysis and clarity in professional objectives. Women rate higher only in food development, traditionally associated with women from household to the food industry. Except for the entrepreneur positions favoring men, these differences were not observed in the employment data one year after graduation. This might be due to the National context where entrepreneurship is associated with masculine traits. Tasks commonly associated with specific genders seem to influence student self-efficacy, but this is not reflected in the employment rate of FIES at least within the evaluated period. Food Industry Engineering is considered atypical within STEM disciplines because more women graduate than men depicting gender roles similar to those in the national context. These results are important for employers, government, and higher education institutions to create strategies to improve self-efficacy among students to reach their full potential as employees and as entrepreneurs to create a better environment for national economic growth.